La Amazonía y el la arte del ingreso en la crisis ambiental - da Costa, Jodival Mauricio (2022)
Two objectives are integrated in this work. The first objective is to discuss the diffusion of values regarding social-environmental responsibility in the current public sphere and how they confer comparative advantages in obtaining differentiated income by companies. The second objective  is to apply this discussion to the Amazon by exemplifying the relationship that Natura company develops with traditional Pan-Amazon communities, as well as the notion of sustainability and how the Amazon can be a strategic region when it comes to environmental crises. The methodology used was based on scientific articles, magazine publications directly linked to the environmental balance of the companies and reports of the Natura company that were published in their website. We concluded that the way to produce market singularities is increasingly due to the combination of production and value diffusion in the public sphere, including the symbolic appropriation of the strategic Spaces of production.